Legal Aspects of Open‑Source Software: A Comparative Study of Google Chrome and Android Platforms - Kazemzadeh, Roya (Law Research Review Quarterly, 2025)
Open‑source software, due to its transparent nature, participatory framework, and high customizability, plays a pivotal role in the development of information technology. This article examines the legal aspects of open‑source software by focusing on two major Google platforms—Google Chrome and Android. The purpose of this study is to conduct a comparative legal analysis of these two platforms and to identify the challenges and opportunities associated with the adoption of the open‑source model. To this end, the paper first defines and conceptualizes key notions such as Free Software and Open‑Source Software, elucidating their underlying nature and philosophical foundations. It then explores the legal frameworks governing such software, including various types of open‑source licenses and the obligations arising therefrom. Subsequently, critical legal concepts such as Copyleft, FOSS (Free and Open‑Source Software), and related issues are analyzed, particularly in light of landmark litigation such as Oracle v. Google. These analyses contribute to a deeper understanding of the legal complexities and the challenges faced by developers and users of open‑source software. Although the general focus of this study is on the legal context of Iran, comparative references are made to jurisdictions with advanced open‑source ecosystems, such as the United States, China, and other jurisdictions. This comparative analysis provides a clear picture of the legal dimensions of open‑source software and the challenges associated with it, offering valuable insights for developers, legal practitioners, and policymakers in achieving a more effective governance and management of open‑source systems.